Potensi Limbah Media Tanam Jamur Tiram dan Jamur Merang sebagai Bahan Baku Pembuatan Kompos Organik - Dhevi Warisaura, Angge; Mukasi Wahyu Kurniawati; Venditias Yudha (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The cultivation of oyster mushrooms (Pleurotus ostreatus) and straw mushrooms (Volvariella volvacea) generates large amounts of organic waste, particularly spent growing media such as baglogs and fermented straw. This study aims to evaluate the effectiveness of combining oyster mushroom baglog waste with straw mushroom cultivation residue in producing high-quality compost. he method used was aerobic composting with seven variations of mixing ratios, supplemented with goat manure and biological activators (M-21 and molasses). The observed parameters included temperature, pH, moisture content, organic carbon content, carbon-to-nitrogen ratio (C/N), and macronutrient content (N + P₂O₅ + K₂O). The results showed that the combination of oyster mushroom waste and straw mushroom waste at a 2:3 ratio produced optimal decomposition conditions, yielding the highest compost quality in accordance with the Indonesian National Standard (SNI). The resulting compost met the quality standards based on SNI 7763:2024, particularly with respect to a maximum C/N ratio of 25, a minimum organic carbon content of 15%, a minimum macronutrient content (N + P₂O₅ + K₂O) of 2%, and a stable, near-neutral pH. These findings suggest that a proportional combination of both types of mushroom waste can serve as an effective and sustainable solution for organic waste management in support of environmentally friendly agriculture.